Effect of Red Bean Extract (Phaseolus Vulgaris L. Sp) on Il-6 Levels and AMH Levels as The Prevention of Premature Ovarian Failure in Mice Model of The Systemic Lupus Erythematosus - Adin Permana; Mukhamad Nooryanto; I Wayan Agung Indrawan; Cholid Rohman Riskianto (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Continuous SLE treatment causes Premature Ovarian Failure (POF) and occurred in 27.3% SLE patients treated with cyclophosphamide. IL-6 plays a critical role in the B cell hyperactivity and immunopathology of human SLE. Phaseolus Vulgaris L. Sp have a high total phenolic content and have been shown to have anti-inflammatory and antioxidant effects. This study’s objective is to prove the effect of red beans (Phaseoulus vulgaris L. sp.) in reducing inflammation (IL-6) and increasing AMH levels. Methods: This is a true experimental design with a post-test-only controlled group design. The sample used in this study was 25 female Babic mice divided in two control groups and three treatment groups. Subjects were given intraperitoneal injection of Pristan (0.5 ml), busulfan (30 mg/kg BW), cyclophosphamide (120 mg/kg BW) to induce POF. ANA test was carried out to prone SLE induction was success. Red bean extract was given at 50 mg/kg BW (in treatment group 1), 75 mg/kg BW (in treatment group 2), and 100 mg/kg BW (in treatment group 3). Data of IL-6 and AMH levels in mice serum were obtained by measurement using ELISA. Results: The study showed a significant difference in ANA levels with a p-value of 0.000 in every sample. The study has proven a significant decrease in IL-6 levels with a p-value of 0.000 and a significant increase in AMH levels at a dose of 100 mg/kg BW (P3) with a p-value of 0.000. Conclusion: Phaseolus vulgaris extract had a significant effect on follicle changes in Balb/c mice in dose of 50 mg/kg and 75 mg/kg but not significantly reduce inflammation (IL-6).